Status norm normalizacyjnych i Polskiego Komitetu Normalizacyjnego – zagadnienia wybrane - Fisher, Bogdan (Kwartalnik Prawa Publicznego, 2015)
The law as a regulator of social relations must use such tools and wording that allow you to specify the social objective, which it should serve. Some fields require specialized technical knowledge, therefore, it is highly difficult to make up-to-date regulations of such areas in legislation. Therefore, the specific determination of these common technical indicators follows the self-regulatory solutions, based on standards and influences the dynamic development of the so-called unorganized sources of administrative law. In this group, there are different normative acts, often of a controversial legal nature, such as e.g. technical standards. The article analyzes the normalization, under which standards are developed by the interested parties within the standardization body for the purpose of voluntary application. Deliberations have been conducted on the doubts about the universality of technical standards, their voluntary or obligatory application, and finally, not treating them as public information. The specific position of Polish Committee for Standardization has been evaluated, as well as the supervision it is subject to and its control mechanisms .